PENGARUH STRUKTUR MODAL, FAKTOR INTERNAL, DAN FAKTOR EKTERNAL TERHADAP NILAI PERUSAHAAN INDUSTRI YANG MASUK BURSA EFEK JAKARTA - Santika, IBM; Ratnawati, Kusuma (JURNAL BISNIS STRATEGI, 2002)
Using financial statement of the manufacture company in Bursa Efek Jakarta and Indonesia macro economic data, this study analyzes impact of internal and external factors on capital structure then on value of the firm in Bursa Efek Jakarta. Factor Analysis and Multiple Regression Analysis are used and found: Both internal and external factors have significant impact on capital structure and value of the firm. The study also found that firm size, financial risk, collateral assets, profitability, and interest rate impact capital structure. Value of the firm is impacted bycapital structure, tax payment, firm size, firm growth, firm uniqueness,profitability, and exchange rate.Â